The Role of Human Resource Management in Improving Employee Performance at CV Indah Fajar Margaasih - Yani Nursolihah (Sean Institute, 2024)
This research aims to find out the role of human resource management in improving the performance of CV Indah Fajar Margaasih employees. The method used in this research is qualitative using data in the form of interviews. The results of this research show that management improves employee performance by providing training to employees which is carried out once every three months in order to improve the skills possessed by the workers. Apart from that, human resource management also checks the quality of the work carried out by employees, which is one way to find out what needs to be improved in the future.